Association Between Adverse Drug Reactions to Anti-Tuberculosis Drugs and Medication Adherence Among Pulmonary Tuberculosis Patients - Sahputri, Juwita; Siregar, Sarah Rahmayani; Azhari, Teuku; Pulungan, Alyifia Yulia Maura (Fakultas Kedokteran Universitas Malikussaleh, 2025)
Tuberculosis (TB) is a significant global public health issue, particularly in developing countries. Indonesia ranks second in the world in terms of TB burden. Adherence to anti-tuberculosis drug (ATD) regimens is crucial for effective TB treatment; however, side drug reactions often hinder adherence. This study examined the relationship between ATD-related side effects and medication adherence among pulmonary tuberculosis patients receiving treatment at the Pulmonary Clinic of RSUCM Aceh Utara. Employing a descriptive analytical design with a cross-sectional approach, we enrolled 74 patients through purposive sampling and collected data using questionnaires. The results showed that most patients experienced minor side effects (70.3%), with urine discoloration (97.3%), nausea (74.3%), and arthralgia (58.1%) being the most common. Patient medication adherence levels were classified as follows: 50% adherent, 29.7% moderately adherent, and 20.3% non-adherent. The chi-square analysis showed a significant statistical link between the side effects of ATD and patients' adherence to their medication regimen (p < 0.001). In conclusion, there is a significant relationship between ATD-related side effects and decreased medication adherence. Proactive management of these side effects and comprehensive patient education are essential. Keywords: anti-tuberculosis drugs; medication adherence; side effects